Gamifying B2B Sales - An Analysis of the Status Quo and Potential for Gamification within Sales - Matthias Schlipf; Michaela Baumann (Marketing Review St.Gallen, 2022)
By means of expert interviews and an online survey experiment among sales representatives, the positive potential of using gamification applications within B2B sales is shown. Based on the empirical results and a derived B2B sales framework, recommendations which gamification elements to apply for which business type and sales phase are presented.
Keywords: 650